Effectiveness of a risk-need-responsivity-based treatment program for violent and sexual offenders: results of a retrospective quasi-experimental study - Seewald, Katharina (Legal and criminological psychology, 2018)
Purpose. Relapse prevention is an important goal in correctional settings. Although there is strong evidence for the effectiveness of certain treatment programs for juvenile offenders, those for adults lack such evidence. This study evaluated the effectiveness of a risk–need–responsivity (RNR)-based intervention. Methods. A quasi-experimental, observational study design and cox regression analysis were used to compare treated violent and sexual offenders (n = 171) with untreated offenders (n = 241). Results. Both groups were observed for an average of 7.9 years. Recidivism rates of treated offenders (11.7%, n = 20) were similar to those of control offenders (15.8%, n = 38; p = .25). When controlling for confounding variables, the hazard of recidivism in the treatment group was 5.2% lower than that in the control group. Subdividing the treatment group resulted in lower hazard ratios for offenders still in therapy when released and offenders cancelling therapy. However, none of the group differences was statistically significant. Conclusion. Our results show that control and RNR-based treatment groups had comparable recidivism rates with a trend towards a positive treatment effect, especially for people in outpatient treatment. However, criminal history, age at the start of follow-up, and actuarial risk of recidivism were significantly associated with recidivism. Future research needs to apply elaborate methodological approaches to detect robust treatment effects and consider different criteria of treatment effectiveness. Furthermore, the influence of prison climate, motivational factors, intervention quality, and factors supporting the success of outpatient treatment should be considered in future studies of larger offender samples.